Descriptive analysis of viability of fuel saving in commercial aircraft through the application of photovoltaic cells - Ramírez Díaz, Gabriel Alberto (2015)
This paper presents the analysis of the technical feasibility to use a photovoltaic system to supply the electrical demand on two referential commercial aircraft, Airbus A340-300 and Cessna Conquest 441. The methodology approach comprises a process given by the selection of the photovoltaic technology, the calculation of the available solar radiation, the determination of the electrical demand, the layout definition of solar cells, the photovoltaic system capacity calculation, the estimation of the photovoltaic system weight, the estimation of fuel savings for photovoltaic system equipped aircrafts, and finally, the extrapolation of results to other aircrafts. The study concludes that the use of photovoltaic technology to supply power to the aircraft electrical system can result viable from the point of view of operational profitability, generating savings in fuel consumption. These fuel savings depend on the type of aircraft, the flying route and schedules of operation.